Defense Logistics Management in Border Areas - Djamarel Hermanto; Herlina Juni Risma Saragih (The Republic of Indonesia Defense University, 2025)
This article thoroughly investigates the optimization of defense logistics management within national border areas, with a distinct focus on integrating a